INFORMATION TRANSPARENCY AS A MODERATION OF FACTORS AFFECTING COMPANY VALUE (for mining companies listed on the IDX in 2019-2024) - Kristiana, Ida; Puspitasari, Noni Chintya; Abdullah, Zailani Bin; Khatik, Nur (Universitas Muhammadiyah Semarang, 2026)
This study aims to determine the effect of intellectual capital, profitability, and company size on company value with information transparency as a moderating variable. This study uses a quantitative method with a sample consisting of 138 mining companies selected through a purposive sampling technique. The study population consists of energy sector companies listed on the Indonesia Stock Exchange during 2019-2024. This analysis method is Moderated Analysis Regression (MRA) using the SPSS 26 application. The results show that intellectual capital has a negative effect on company value, profitability has a positive effect on company value, and company size has no effect on company value. Information transparency is not able to moderate the relationship between intellectual capital and company value. Information transparency is able to moderate by weakening the relationship between profitability and company value, while information transparency is able to moderate by strengthening the relationship between company size and company value.